Feasibility of ending tuberculosis in Shangrao City through active intervention measures: a mathematical study - Xu, Mingshu; He, Yue; Liu, Qiao; Chen, Qiuping; Zhao, Zeyu; Xu, Zheng; Shu, Chongfei; Xia, Jun; Yang, Yuyan; Gavotte, Laurent; Frutos, Roger; Ye, Huiming; et al. (Frontiers in Public Health, 2025)
ObjectiveChina faces significant challenges in ending tuberculosis (TB). Active case finding (ACF) and TB preventive therapy (TPT) have proven to be critical measures in reducing TB incidence. This study uses a transmission dynamics model to identify the optimal intervention strategies for achieving WHO’s TB elimination targets in Shangrao City. The findings guide targeted TB control efforts in similar settings.MethodsTo account for COVID-19 pandemic disruptions, we first used a seasonal autoregressive integrated moving average (SARIMA) model to predict and substitute the reported TB incidence during 2020–2023. Subsequently, we developed an age-stratified dynamic transmission model using surveillance data from Shangrao City’s Infectious Diseases Reporting System (IDRS) between 2008 and 2023 to evaluate tuberculosis transmission patterns across age groups. The model assessed the effectiveness of key interventions including active case finding (ACF), latent tuberculosis infection (LTBI) screening, and tuberculosis preventive treatment (TPT).ResultsThe model fit well with the reported data (R2 = 0.53, p < 0.001). Preventive treatment measures can fully achieve the goal of reducing incidence. All five TPT regimens showed potential to meet the TB elimination targets, with the 3HP regimen (weekly rifapentine + isoniazid for 3 months) performing the best. With the proportion of post-detection consent to TPT of 0.6 and rate of LTBI screening of 0.5, the 3HP regimen met the 2030 and 2035 incidence targets, with projected rates of 15.27/100,000 and 7.98/100,000, respectively.ConclusionThe current TB control efforts face significant challenges, with a considerable gap remaining in achieving TB elimination targets. Combining ACF with TPT presents a promising strategy to reach these goals. Older tuberculosis (TB) patients constitute a high-risk population, and effective prevention and treatment in this group are critical to achieving future TB elimination goals. To reduce the risk of recurrence and reinfection, enhanced follow-up monitoring of older patients should be prioritised alongside targeted health education interventions tailored to high-risk groups.